1979
DOI: 10.1136/bjsm.13.4.156
|View full text |Cite
|
Sign up to set email alerts
|

A survey of badminton injuries.

Abstract: A Badminton Injury Questionnaire (BIQ) was developed to survey the type and frequency of injuries that are likely to occur from playing competitive badminton. Two hundred and thirty-one players, ranging from club players to international champions, completed the survey which indicated an injury incidence rate of .09 and .14 injuries per person per year for male and female badminton players respectively.Badminton participation resulted in relatively few injuries, most of which were cramps, blisters, strains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 4 publications
3
53
0
3
Order By: Relevance
“…Hensley and Paup (1979) reported that the incidence rate in terms of injuries per person per year for male and female competitive badminton players were 0.09 and 0.14 respectively. Jorgensen and Winge (1990) reported that injury rate was higher in training than in competition, which was in contrast to most other sports, i.e., Brooks et al reported that the injury incidence in the professional English Rugby union was 91 per 1000 player-hours in match (Brooks et al 2005a) and was 2.0 per 1000 player-hours in training (Brooks et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hensley and Paup (1979) reported that the incidence rate in terms of injuries per person per year for male and female competitive badminton players were 0.09 and 0.14 respectively. Jorgensen and Winge (1990) reported that injury rate was higher in training than in competition, which was in contrast to most other sports, i.e., Brooks et al reported that the injury incidence in the professional English Rugby union was 91 per 1000 player-hours in match (Brooks et al 2005a) and was 2.0 per 1000 player-hours in training (Brooks et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reported badminton injuries from epidemiology surveys and case studies included Achilles tendon rupture (Fahlstrom et al 1998a), ankle ligamentous sprain (Fahlstrom et al 1998b;Hoy et al 1994), ankle fracture (Hoy et al 1994), eye trauma (McWhae and LaRoche 1990), shoulder impingement (Lo et al 1990), shoulder dislocation (Hazmy and Parwathi 2005), wrist injuries (Helal 1978), tennis elbow (Jorgensen and Winge 1990), muscle cramps, blisters and strains (Hensley and Paup 1979). Among all these injuries, epidemiology studies showed that the mostly injured sites were ankle (23.5%), knee (14.0%), foot (12.5%), arm (8.5%) and leg (5.4%) (Fong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Badminton requires jumps, lunges, quick changes in direction, and rapid arm movements in order to stroke the shuttlecock from a variety of postural positions (Hensley & Paup, 1979). Thus, the physical demands of a competitive game of badminton suggest that injuries to the limbs may be a prevalent ailment (Hensley & Paup, 1979). Blisters, muscle cramps, muscle strains or tears, bruises, sprains or ligament injuries, tendonitis or other tendon injuries, bursitis were reported from badminton players (Miyake 2016, Hensley & Paup 1979.…”
Section: General Instructionsmentioning
confidence: 99%
“…Sports-related injuries can have a substantial impact on the long-term health of student-athletes (Zachary et al, 2015). Badminton requires jumps, lunges, quick changes in direction, and rapid arm movements in order to stroke the shuttlecock from a variety of postural positions (Hensley & Paup, 1979). Thus, the physical demands of a competitive game of badminton suggest that injuries to the limbs may be a prevalent ailment (Hensley & Paup, 1979).…”
Section: General Instructionsmentioning
confidence: 99%
“…Various factors such as high repetition of motions, high muscular forces and extreme elbow positions affect the peripheral nervous system with or without signs and symptoms 6 . The epidemiological data reporting studies related to badminton and lawn tennis injuries have shown that these injuries often are severe in character but of relatively low frequency 7,8 . But there is very sparse literature available on injuries related to playing table tennis.…”
Section: Introductionmentioning
confidence: 99%